Integrating MaxEnt with chemometrics to evaluate the impact of environmental variables on the coumarin content and the distribution of Angelica dahurica - Gan, Zhengkun; Ma, Jun; Liu, Xinyu; Luo, Jiaxin; Li, Junke; Pu, Lili; Jiang, Guihua; Lian, Yan (Frontiers in Plant Science, 2025)
IntroductionAngelica dahurica is a traditional medicinal plant known for its high content of bioactive coumarins. With climate change potentially affecting both species distribution and secondary metabolite accumulation, there is a pressing need to integrate ecological and chemical data to guide future cultivation and resource utilization strategies.MethodsThis study combined the Maximum Entropy (MaxEnt) ecological modeling approach with chemometric analysis to (i) predict the suitable habitat distribution of A. dahurica under current and future climate scenarios and (ii) evaluate the correlation between environmental variables and coumarin accumulation.Results(1) The key environmental variables influencing the distribution of A. dahurica were identified as BIO_13 (precipitation of the wettest month), BIO_11 (mean temperature of the coldest quarter), and elevation (DEM). (2) Presently, the highly suitable regions for A. dahurica cultivation are mainly in Sichuan, Henan, and Hebei provinces. (3) Under future climate scenarios, the highly suitable habitats are expected to expand and shift geographically, especially toward Henan and Jiaozuo, with parts of Hubei, Shaanxi, and Shandong transitioning into highly suitable zones. (4) Chemometric analyses revealed that A. dahurica samples from highly suitable areas contained significantly higher total coumarin content than those from medium-suitability regions. (5) A strong correlation was observed between key environmental factors (especially BIO_11 and DEM) and the relative content of five major coumarin components.(6) Spatial mapping of chemical composition indicated distinct regional differences in coumarin distribution, suggesting the potential for geoherbalism-based classification.DiscussionThe integration of ecological modeling with chemical analysis provides a powerful framework for understanding the impact of environmental variables on both the distribution and chemical quality of A. dahurica. These findings offer valuable guidance for targeted cultivation and resource management under future climate change conditions.